A New Crater Near InSight: Implications for Seismic Impact Detectability on Mars. Issue 8 (19th August 2020) - Daubar, I. J.; Lognonné, P.; Teanby, N. A.; Collins, G. S.; Clinton, J.; Stähler, S.; Spiga, A.; Karakostas, F.; Ceylan, S.; Malin, M.; McEwen, A. S.; Maguire, R.; et al.
Abstract: A new 1.5 m diameter impact crater was discovered on Mars only ~40 km from the InSight lander. Context camera images constrained its formation between 21 February and 6 April 2019; follow‐up High Resolution Imaging Science Experiment images resolved the crater. During this time period, three seismic events were identified in InSight data. We derive expected seismic signal characteristics and use them to evaluate each of the seismic events. However, none of them can definitively be associated with this source. Atmospheric perturbations are generally expected to be generated during impacts; however, in this case, no signal could be identified as related to the known impact. Using scaling relationships based on the terrestrial and lunar analogs and numerical modeling, we predict the amplitude, peak frequency, and duration of the seismic signal that would have emanated from this impact. The predicted amplitude falls near the lowest levels of the measured seismometer noise for the predicted frequency. Hence, it is not surprising this impact event was not positively identified in the seismic data. Finding this crater was a lucky event as its formation this close to InSight has a probability of only ~0.2, and the odds of capturing it in before and after images are extremely low. We revisit impact‐seismic discriminators in light of real experience with a seismometer on the Martian surface. Using measured noise of the instrument, we revise our previous prediction of seismic impact detections downward, from ~a few to tens, to just ~2 per Earth year, still with an order of magnitude uncertainty. Plain Language Summary: A small new impact crater was discovered on Mars very close to the InSight lander. Photographs from a camera in orbit show it formed between 21 February and 6 April 2019. Three seismic events were detected by InSight during this time. We estimate what seismic data from the impact would have looked like and whether or not each of the seismic events was caused by the new impact, but none of them can be definitely linked. We predict the size, frequency, and length of time of the signal that would have come from this impact. Even though this impact is very close to InSight, it is small, so it was not a large seismic event. The signal would be near the quietest the instrument ever gets. There is only a 1 in 5 chance each Earth year that a crater would have formed this close to InSight, and a much lower chance that it would be imaged; thus, we were very lucky to find this crater. Using what we know about the instrument on the ground, we update the number of impacts we expect to find with InSight to ~2 each Earth year, with a lot of uncertainty. Key Points: A new 1.5 m diameter impact crater formed on Mars ~40 km from the InSight lander between February and April 2019 Three candidate seismic events occurred during this time frame, but none of them can be definitively associated with the new crater We revise our expectations for InSight impact detections above the background noise to be ~2 per Earth year, with large uncertainties